Piezoelectric Microgenerator Rectifying Circuit Simulation Using LTspice - Mustapha, Ain Atiqa; Mat Ali , Noraini; Kok, Swee Leong (2013)
Energy harvesting using piezoelectric becomes popular due to its miniature size and have the potential to replace the used of battery that has limited lifespan. One of the methods in harvesting ambient energy is through the form of vibration energy. The vibration energy is then converted into electrical energy. In this paper, a piezoelectric generator system is designed to harvest energy from ambient environment at specific vibrational frequency. The AC output from piezoelectric is rectified using a bridge rectifier and then stored in a supercapacitor. The simulation results using LTspice has shown a promising outcome with an output voltage reaching 8 V using LTC 4358 with an internal 20mΩ N-channel MOSFET.